What are Convention Attendees Looking for? An Examination of the Impact of Perceived Value and Value Co-creation on Attitude Formation - Ho, Jie Min; Sia, Joseph Kee Ming; Lee, Sean; Yap, Ching Seng (Cognizant Communication Corporation, 2021)
Despite convention tourism is becoming an important segment of the tourism industry in many countries, the specific benefits that convention attendees see valuable when attending conventions are inconclusive. Based on the consumption values theory, this study considers the impacts of two types of value: perceived value and value of co-creation on convention attendees’ attitude formation. Derived from a sample of 434 convention attendees and Partial Least Squares Structural Equation Modelling (PLS-SEM) analysis, results indicate that value of co-creation, together with another two dimensions of perceived value, emotional value and functional value, have significant influences on convention attendees’ attitude towards the convention attended. Particularly, it was found that perceived value by itself had limited effects in contributing the positive attitude towards conventions in the contemporary business world as consumers today are increasingly prefer co-creation of value and collaboration with service providers. The study contributes to the convention tourism literature by being the first to incorporate both perceived value and value of co-creation within the same model and testing related hypotheses. The results may facilitate decision-making and strategic development of tourism-related investments among convention organisers, destination marketing organisations and government agencies, which can eventually strengthen a country’s competitive edge in attracting convention attendees.